Branding beyond the gender binary. Issue 8 (12th May 2022) - Cooke, Angelica; Russell‐Bennett, Rebekah; Wang, Di; Whyte, Stephen
Abstract: Gender is a fundamental pillar of personal identity, and as such, gendered brand personality is an equally important aspect of brand identity, as it enables consumers to express their gender identity through consumption. However, as gender attitudes and identities change to reflect the broader culture, marketers must continuously re‐evaluate how changing gender attitudes and identities will impact consumers' responses to gendered brands. This paper examines the effect of congruence between Gendered Brand Personality and consumer psychological gender on brand outcomes using two online experiments with USA and UK samples. Our findings indicate that congruence between brand gender and psychological gender increases brand equity and purchase intention in brand gender communication contexts including through logo, model, and usage setting. This congruence effect is driven by consumer self‐referencing. A follow‐up qualitative study using a focus group adds additional insights for the congruence effect in terms of potential boundary conditions and alternative underlying mechanisms beyond self‐referencing. These findings suggest that marketers should design their own brand personality to be in line with target consumers' psychological gender.